The Relationship Between Circulating Growth Differentiation Factor 15 Levels and Diabetic Retinopathy in Patients With Type 2 Diabetes - Niu, Yixin; Zhang, Weiwei; Shi, Jie; Liu, Yueming; Zhang, Hongmei; Lin, Ning; Li, Xiaoyong; Qin, Li; Yang, Zhen; Su, Qing (Frontiers in Endocrinology, 2021)
Objective Growth differentiation factor 15 (GDF-15) is a member of the TGF-β superfamily that has anti-inflammatory properties. The objective of this study was to evaluate the relationship between circulating GDF-15 levels and diabetic retinopathy (DR) in patients with type 2 diabetes. Materials/Methods A case–control study was performed in which 402 patients with type 2 diabetes were enrolled. Of these, 171 patients had DR and the remaining 231 patients without DR acted as controls. The plasma GDF-15 levels were measured using ELISA, while DR was diagnosed using the canon ophthalmic digital imaging system and the Canon EOS 10D digital camera (Canon, Tokyo, Japan) through a non-pharmacologically dilated pupil. Results The levels of GDF-15 were significantly higher in patients with DR [168.9 (112.9–228.3) pg/ml vs. 127.8 (96.1–202.8) pg/ml, P < 0.001] compared to controls. Results of the Spearman correlation analysis showed that the GDF-15 levels were positively associated with the duration of diabetes morbidity, fasting plasma glucose, systolic blood pressure, albumin/creatinine ratio, creatinine, and liver enzymes, but negatively associated with eGFR (both P < 0.001). The participants in the highest GDF-15 quartile had a significantly increased risk for DR (OR = 2.15, 95% CI 1.53–3.02) after adjusting for potential cofounders. Conclusions The circulating GDF-15 levels are positively associated with DR independent of potential cofounders.